Integrated Methylome and Transcriptome Analyses Reveal the Molecular Mechanism by Which DNA Methylation Regulates Kenaf Flowering - Li, Zengqiang; Tang, Meiqiong; Luo, Dengjie; Kashif, Muhammad Haneef; Cao, Shan; Zhang, Wenxian; Hu, Yali; Huang, Zhen; Yue, Jiao; Li, Ru; Chen, Peng (Frontiers in Plant Science, 2021)
DNA methylation regulates key biological processes in plants. In this study, kenaf seedlings were pretreated with the DNA methylation inhibitor 5-azacytidine (5-azaC) (at 0, 100, 200, 400, 600 μM), and 200 μM 5-azaC pretreatment most effectively promoted flowering. To reveal the underlying mechanism, the phytohormone, ATP, and starch contents were determined, and genome-wide DNA methylation and transcriptome analyses were performed using anthers under 200 μM 5-azaC pretreatment (5-azaC200) and control (5-azaC0) conditions. Biochemical determination showed that 5-azaC pretreatment significantly reduced indoleacetic acid (IAA) and gibberellic acid (GA) contents and significantly increased abscisic acid (ABA) and ATP contents. The starch contents were significantly increased with 200 μM and 600 μM 5-azaC. Further genome-wide DNA methylation analysis revealed 451 differentially methylated genes (DMGs) with 209 up- and 242 downregulated genes. Transcriptome analysis showed 3,986 differentially expressed genes (DEGs), with 2,171 up- and 1,815 downregulated genes. Integrated genome-wide DNA methylation and transcriptome analyses revealed 72 genes that were both DMGs and DEGs. These genes, including ARF, PP2C, starch synthase, FLC, PIF1, AGL80, and WRKY32, are mainly involved in plant hormone signal transduction, starch and sucrose metabolism, and flowering regulation and may be involved in the early flowering phenomenon. This study provides a reference and theoretical basis for kenaf production and insights into DNA methylation effects on crop growth and development.